Sulfur Chemistry in Early Star-forming Cores: A Non-LTE Analysis of SO 2 and SO - Paron, Sergio Ariel (2025)
The chemical behavior of sulfur in the interstellar medium (ISM), particularly in the dense regions where stars form, is still far from being well understood. Questions such as which is the main sulfur reservoir in the ISM remain unanswered. Studying interstellar sulfur-bearing molecules contributes to understanding the chemical behavior of this element in the ISM. Star-forming regions in their most early phases, when complex interstellar chemistry begins to activate, are favorable sites to carry out this type of research. We present results which are complementary to recent, extensive work which made use of data from the Atacama Large Millimeter Array. We focus on the emission of SO2 and SO obtained toward 37 dense molecular cores embedded in cold clumps. Through an analysis of non–local thermodynamic equilibrium (non-LTE), the abundances of these molecular species were estimated. In general a good agreement was obtained with the LTE results previously presented.